Point-of-care tests in general practice: Hope or hype?. (December 2013) - Cals, Jochen; van Weert, Henk
Abstract Point-of-care tests are biomedical tests on patients' specimens like blood, saliva, urine or faeces, which can be used near the patient, without interference of a laboratory. The use of these tests, many of which have been recently developed, is increasing in general practice, where they add to the GP's set of diagnostic instruments. The question is, however, whether they always contribute to an effective and high-quality diagnostic process by GPs. We present a set of criteria that can be used by guideline developers, regional primary care organizations and individual GPs to evaluate a new point-of-care test in a practice setting. These criteria do not relate only to their use and quality. A point-of-care test needs to be evaluated in the right population and for the right indications, and GPs then need to use them for the indications for which they were evaluated. Expanding the range of indications can lead to an increase in false-positive and false-negative test results.